Growth constraints and external vulnerability in Argentina - Catelén, Ana Laura (2020)
This paper describes the balance-of-payments dominance as a growth constraint to the Argentinian economy and briefly characterizes the unbalanced productive structure of the country as its main cause. Also, understanding that under this constraint domestic economic cycles depend on external shocks, auto-regressive vectors are used to characterize the short-run impact of these shocks on GDP, trade balance, and real wages. Results confirm that there is a bottleneck in the trade balance that blocks future growth possibilities, that GDP and wages are highly sensitive to variations in the terms of trade, that the increase in external debt does not produce economic growth or improvements in the purchasing power of the population, and that there is a vicious dynamic between capital flight and foreign debt. At the same time, there is evidence of the increase in external vulnerability since the change in the accumulation model in the 1970s.